Spectra of cosmic ray electrons and positrons in the Galaxy - Lagutin, A.A.; Osadchiy, K.I.; Gerasimov, V.V. (Вопросы атомной науки и техники, 2001)
A new study of the cosmic ray electron and positron spectra is presented, using an anomalous diffusion model to describe the particles propagation in the Galaxy. The parameters defining the anomalous diffusion have been recently determined from the study of nuclei propagation. The computed electron and positron spectra under assumption that positrons, as well as electrons, are accelerated by a galactic source, are in a good agreement with the measurements. The source spectral index, found from experimental data, in this approach turns out to be equal to 2.95 for electrons and positrons. The predicted positron fraction e⁺/(e⁺+e⁻) in high energy region E≈10² ÷10³ GeV is ~0.06.